2014
DOI: 10.1007/s00167-014-2969-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of accuracy of robotically assisted unicompartmental arthroplasty

Abstract: Robotic-assisted medial UKA results in accurate prosthesis position. Inaccuracy may be attributed to suboptimal cementing technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…4,5,7,8,[28][29][30] Although a financial analysis has not been undertaken, our findings do show important differences in inpatient rehabilitation and hospital stay, which will aid healthcare policy makers in the allocation of medical resources and cost planning for the implementation of this technology into clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…4,5,7,8,[28][29][30] Although a financial analysis has not been undertaken, our findings do show important differences in inpatient rehabilitation and hospital stay, which will aid healthcare policy makers in the allocation of medical resources and cost planning for the implementation of this technology into clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…However, suboptimal cementing technique may cause mismatch in image-based alignment and postoperatively measured alignment. 23 There is controversy about the optimal postoperative mechanical axis. However, there is agreement that overcorrection in a valgus deformity and undercorrection of <10 degrees varus should be avoided.…”
Section: Technique For Ukamentioning
confidence: 99%
“…Recently, Mofidi et al 31 reported on a series of 232 medial UKRs followed retrospectively to assess the accuracy of component placement using the MAKO system. They compared planned intra-operative robotic alignment with post-operative alignment on standardized radiographs and found 70% of prosthesis were inserted within 3 of where intended in the coronal and sagittal planes.…”
Section: Haptic Robotic Systemsmentioning
confidence: 99%